Analisis Biaya Menurut Variable Costing Untuk Pengambilan Keputusan Menerima Atau Menolak Pesanan Khusus Pada Perusahaan Kue Bangket Tokin - Pongantung, Artika K.; Manoppo, Wilfried S.; Mangindaan, Joan (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
The purpose of this study is (1) To know the elements of cost calculated in the variable cost component (2) To know how the calculation of cost analysis according to the costing variables for decision making accept or reject the special order and (3) Whether the application of such calculations can affect the increase in corporate profits. This research uses quantitative descriptive analysis method. The data sought in this study is a special production order production report which will be used for decision making accept or reject special order obtained based on interview result and observation. Based on the calculation of cost analysis according to variable costing for decision making accept or reject special order, the variable cost the production of cake is Rp. 358.224.560 and for a fixed cost is Rp. 422.398.305. And the result of the analysis on the use of variable costing in relation to differential cost analysisÂ  to accept or reject the special orders, from RM. Setia Amurang and bali souvenir, total profit of Rp. 7.915.068. The shows that from the alternatives used can provide benefits for the company, when receiving special order. The leader of the tokin cake cooking company, should receive a special order with the cost request by the subscriber and consider the revenue and the differential cost to generate profit contribution.